Millennial Generation Consumer Preferences and Perceptions of Halal Cosmetics (Case Study at Nurul Jadid Islamic Boarding School) - Saifuddin Saifuddin; Sitti Aisyah (Nurul Jadid University, 2021)
On cosmetic products, the halal label indicates a product made from ingredients that do not contain haram elements. The halalness of cosmetic products is also determined by the manufacturing process. Although using parts of animals that are categorized as halal, these animals must be ensured that they have been processed according to Islamic law. This study uses a qualitative descriptive method that aims to determine the preferences and perceptions of millennial consumers towards halal cosmetics at the Nurul Jadid Islamic Boarding School. The results of this study indicate that students or millennial generation consumers in Islamic boarding schools have the same preferences and perceptions of halal cosmetics, namely prioritizing the halalness of every cosmetic product that will be consumed, even though there are one or several of the students who use cosmetics whose halalness is not clear. But so far, the boarding school has guaranteed the halalness of every cosmetic product sold in the boarding school environment, because all the shops that operate in the boarding school environment have been confirmed to sell halal products that are allowed in Islam in accordance with the sharia.